Interaction patterns in online/distance learning at higher education: A case study of biology education - Sapriati, Amalia; Rahayu, Ucu; Kismiati, Dyah Aniza; Zakirman, Zakirman (Jurnal Cakrawala Pendidikan, 2024)
This study investigates tutor-student interaction patterns in online learning environments, aiming to unveil effective strategies for optimising the online educational experience. Guided by a qualitative approach employing a case study design, this study delves into the interaction and written communication dynamics among 65 students and their tutors participating in four-course programs within the biology education study program. The observational and analytical phases focused on unravelling the nuances of online interactions. Subsequently, follow-up interviews were conducted to glean deeper insights and understanding into the observed patterns of communication and engagement between students and tutors. Through the qualitative analysis procedure, five distinct interaction patterns emerged from the analysis, ranging from tutor-initiated questions to collaborative exchanges among students and tutors. Each pattern offers unique insights into fostering engagement, feedback, and peer-to-peer learning dynamics. As online education continues to evolve, understanding and leveraging these identified tutor-student interaction patterns provide valuable insights for educators and instructional designers. Recognising the diverse ways in which interactions unfold is instrumental in enhancing the quality and effectiveness of online learning, fostering student engagement, and achieving the overarching goals of online education.